2020
DOI: 10.3390/biom10070992
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Opioid Receptors in the Antihypertensive Effect of a Novel Chicken Foot-Derived Peptide

Abstract: The peptide AVFQHNCQE demonstrated to produce nitric oxide-mediated antihypertensive effect. This study investigates the bioavailability and the opioid-like activity of this peptide after its oral administration. For this purpose, in silico and in vitro approaches were used to study the peptide susceptibility to GI digestion. In addition, AVFQHNCQE absorption was studied both in vitro by using Caco-2 cell monolayers and in vivo evaluating peptide presence in plasma from Wistar rats by ultra-high perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In this regard, the peptides QVGPLIGRYCG and AVFQHNCQE, isolated from a Protamex ® -digested foot hydrolysate, showed antihypertensive effects in SHR (10 mg/kg BW), exerting the maximum BP reduction at 6 h post administration (−10.94 and −25.07 mmHg, respectively) [ 22 ]. Additional studies showed that AVFQHNCQE, which is hydrolyzed during gastrointestinal digestion and seems not to be absorbed by gastrointestinal tract, displays an antihypertensive action through an increase in NO levels, which is mediated by the activation of opioid receptors [ 135 ]. After the administration of this peptide, SHR also showed an improvement in endothelial dysfunction and a reduction in oxidative stress markers with respect to water controls [ 136 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the peptides QVGPLIGRYCG and AVFQHNCQE, isolated from a Protamex ® -digested foot hydrolysate, showed antihypertensive effects in SHR (10 mg/kg BW), exerting the maximum BP reduction at 6 h post administration (−10.94 and −25.07 mmHg, respectively) [ 22 ]. Additional studies showed that AVFQHNCQE, which is hydrolyzed during gastrointestinal digestion and seems not to be absorbed by gastrointestinal tract, displays an antihypertensive action through an increase in NO levels, which is mediated by the activation of opioid receptors [ 135 ]. After the administration of this peptide, SHR also showed an improvement in endothelial dysfunction and a reduction in oxidative stress markers with respect to water controls [ 136 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the ACEi effect of the five antihypertensive amino-acid sequences isolated from chicken byproduct hydrolysates, the BP-lowering effects of these peptides could not be related to a specific amino-acid profile. Thus, their in vivo effects may be a consequence of the peptide-derived fragments released during the gastrointestinal enzymatic digestion of the chicken peptides, as seen for the amino-acid sequences AVFQHNCQE or VSKRLNGDA [ 85 , 135 ].…”
Section: Resultsmentioning
confidence: 99%
“…The delivery of antihypertensive peptides by the oral route presented many challenges. For example, the gastrointestinal proteases, the low pH environment in the stomach, and the efficiency of intestinal absorption often affect the performance of antihypertensive peptides [ 28 ]. Oral drugs are generally not bioavailable or bioactive due to these factors.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, to demonstrate the participation of NO in the antihypertensive effect, oral administration of the peptide Ala-Val-Phe-Gln-His-Asn-Cys-Gln-Glu derived from Hpp11 at doses of 10 mg/kg in rats negatively regulated the expression of the aortic gene of the vasoconstrictor factor ET-1 and the main endothelial producer of NOX4 free radicals ( Mas-Capdevila et al, 2019b ). In addition, it was determined that the Ala-Val-Phe-Gln-His-Asn-Cys-Gln-Glu peptide requires absorption to have an effect on blood pressure, demonstrating that its antihypertensive effect is mediated by NO through its interaction with opioid receptors ( Mas-Capdevila et al, 2020 ). Some bioactive peptides could mediate their physiologic effects through binding to receptors present in the intestinal wall ( Hernández-Ledesma et al, 2011 ).…”
Section: Biological Activities Of Peptides Obtained From Poultry By-p...mentioning
confidence: 99%
“…The most recent research involves oral administration of hydrolyzed cartilage extract in the prevention of osteoarthritis ( Ma et al, 2021 ). Studies have also shown effects in the prevention of cardiovascular diseases ( Wu et al, 2020 ) and chronic liver diseases ( Chen et al, 2017 , Lin et al, 2017 , Wu et al, 2021 ), in antihypertensive treatments ( Bravo et al, 2019 , Mas-Capdevila et al, 2020 ), in the regulation of lipid metabolism as alternative treatments for obesity ( Yang et al, 2014 ) and to obtain antioxidant agents ( Chou et al, 2014 ).…”
Section: Biological Activities Of Peptides Obtained From Poultry By-p...mentioning
confidence: 99%